Nurses’ perception of futile care: A narrative review - Amir Rezaie; Fatemeh Molayi; Maryam Sadat Shaafi; Mojtaba Ghanbari Ghalesar (Journal of Nursing Advances in Clinical Sciences, 2024)
The continuous medical and health sciences advancement has significantly increased patient survival rates. However, prolonging life without improving its quality in terminally ill patients has become a challenging issue for care providers, particularly nurses, who are required to determine the futility or effectiveness of care. This study explores and identifies nurses' perceptions of futile care based on the existing scientific literature. In this review study, an online search was conducted to find studies published between 2010 and 2023 that examined the perception of nurses regarding futile care. Databases including Scientific Information Database, Education Resources Information Center, Science Direct, PubMed, IranMedex, and Google Scholar were searched using the keywords "Futile Care", "Perception of Futile Care", "End-of-Life Care", "Perception", and "Nurses". Four main themes emerged from the review, including the definition of futile care, decision-making, limitations, and outcomes related to futile care, encompassing 13 subcategories. Futile care is not easily defined, and the ethical dilemmas surrounding this phenomenon are highly complex. Considering the critical role of nurses in patient care and end-of-life decision-making and their significant influence on patients' and families' perspectives, it is essential to enhance education, support services, and counseling for healthcare professionals regarding medical futility and related ethical issues.